Development of Organic Waste Processing Module of Eco-Enzyme Project-Based Learning Materials for Students - Rahmawati, Fitri (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to develop a project-based teaching module on the production of eco-enzyme within the topic of organic waste processing for students of the Biology Education Study Program, FKIP Universitas Cordova, in the Environmental Science Fundamentals course. This research is a development study using the 4D model, consisting of the stages of define, design, develop, and disseminate. However, in this study, the process was limited only to the development stage. The results showed that the module was declared valid and feasible to use based on validation results from two expert validators (a material expert and a media expert), with a validity percentage of 77,5%, as well as a module readability test by students of 85%, indicating that the module is easy to understand. The validation results indicate that the project-based eco-enzyme production teaching module is appropriate and can be implemented in the learning process.